Rancang Bangun Media Informasi Berbasis Multimedia Untuk Mencegah Risiko Stunting Pada Anak Balita - Alamsyah, R. Yadi Rakhman; Nursyanti, Reni; Putri, Resvina Alya (INTERNAL (Information System Journal), 2023)
Stunting is a growth disorder that describes the failure to growth potential as a result of inadequate health status or nutrition. Child stunting data in 2022 has fallen to 21.6%, but according to the World Health Organization (WHO) criteria, the percentage is still high (20%). One prevention in reducing the risk of stunting is to increase the knowledge of parents about stunting and the intake of good food to be consumed by children. The dissemination of information about stunting and nutritional food intake is often found in the media of information such as text, video, and images but the distribution of information is not organized in one medium. The development phase uses the Multimedia Development Life Cycle (MDLC) methodology with five (five) stages: concept, design, material collection, assembly, and testing. The result of this study is a multimedia-based information media in dasawisma RT 05 Bumi Orange, Cimekar Village, Bandung Regency, with a selection of stunting material menus including complementary foods for breast milk (MPASI), children's weight and height standards, child nutrition, and food intake.